2018
DOI: 10.1038/s41598-018-25574-7
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Clinical Trial with Ex Vivo Expanded Recipient Regulatory T cells in Living Donor Kidney Transplants

Abstract: There is considerable interest in therapeutic transfer of regulatory T cells (Tregs) for controlling aberrant immune responses. Initial clinical trials have shown the safety of Tregs in hematopoietic stem cell transplant recipients and subjects with juvenile diabetes. Our hypothesis is that infusion(s) of Tregs may induce transplant tolerance thus avoiding long-term use of toxic immunosuppressive agents that cause increased morbidity/mortality. Towards testing our hypothesis, we conducted a phase I dose escala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
223
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(227 citation statements)
references
References 53 publications
4
223
0
Order By: Relevance
“…Clinical studies have demonstrated the safety of Treg adoptive transfer in graft‐versus‐host disease and type 1 diabetes mellitus . Furthermore, a number of trials have been initiated both in kidney and in liver transplantation . Liver transplantation constitutes an appealing clinical setting to evaluate the effects of Treg transfer given the lower immunogenicity of liver allografts and the substantial clinical experience that has been derived from trials of complete immunosuppression discontinuation .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have demonstrated the safety of Treg adoptive transfer in graft‐versus‐host disease and type 1 diabetes mellitus . Furthermore, a number of trials have been initiated both in kidney and in liver transplantation . Liver transplantation constitutes an appealing clinical setting to evaluate the effects of Treg transfer given the lower immunogenicity of liver allografts and the substantial clinical experience that has been derived from trials of complete immunosuppression discontinuation .…”
Section: Introductionmentioning
confidence: 99%
“…Eight-Treg, supported by the ReSHAPE consortium, and that will take place in 2021 2 (https ://www.resha pe-h2020.eu/) (Figure 2 145 This rational strategy will be applied to the Eight-Treg clinical trial.…”
Section: Cd8 + Treg Clini C Al Trial In K Idne Y Tr An S Pl Anted Pmentioning
confidence: 99%
“…148,149 However, Tregs have the potential to immunosuppress recipients and make them prone to infections and malignancy. 148,149 However, Tregs have the potential to immunosuppress recipients and make them prone to infections and malignancy.…”
Section: Limitati On S Of Reg Ul Atory T Cell Ther Apy Following Lumentioning
confidence: 99%
“…148,149 However, Tregs have the potential to immunosuppress recipients and make them prone to infections and malignancy. 149 At this time, we do not understand if the efficacy seen in preclinical models of lung transplantation is due to antigen-specific immunosuppression or, instead, general suppression of inflammation within the graft microenvironment. Fortunately, methods have already been devised that manufacture clinical grade alloantigen-specific Tregs, such as the darTregs discussed above.…”
Section: Limitati On S Of Reg Ul Atory T Cell Ther Apy Following Lumentioning
confidence: 99%